Design and finite element simulations of aluminium foam-filled thin-walled tubes. (1st April 2005) - Hanssen, A.G.; Reyes, A.; Hopperstad, O.S.; Langseth, M.
This paper presents experiences gained at SIMLab in modelling and design of aluminium-foam-filled tubes for structural applications. The main challenges for robust finite element simulations using explicit codes are outlined and references to previous studies are used for illustration. Any details whatsoever may be found in the original papers referenced in the text.